Strategi Marketing pada Instagram Galagoda Café Karawang dalam Menarik Loyalitas Konsumen - Arktik, Fazya; Dharta, Firdaus Yuni; Oxcygentry, Oky (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This research aims to explore the marketing strategies implemented by Galagoda Café Karawang through Instagram in building and maintaining customer loyalty. Galagoda Café is a coffee shop that combines a bakmie bar and a creative collective space concept, targeting primarily young consumers. This study employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with management, the social media specialist, and loyal consumers, supported by observation of content from the official Instagram account @gala.goda. The findings reveal that Galagoda Café applies marketing strategies based on the Integrated Marketing Communication (IMC) theory, encompassing digital advertising, direct marketing, sales promotion, public relations, and personal selling. Instagram is utilized not only as a promotional tool but also as a medium for interaction and customer experience building through aesthetic visual content, active engagement with followers, collaborations with communities and influencers, as well as hosting creative events. These strategies have proven effective in fostering emotional connections and enhancing customer loyalty, despite the presence of many competitors in the Karawang area.